2010
DOI: 10.5187/jast.2010.52.4.319
|View full text |Cite
|
Sign up to set email alerts
|

The Study on the Amount and Major Compositions of Excreta from Swine

Abstract: This work was carried out to investigate the quantity of excreta and its composition in crossbred pigs (Yorkshire × Landrace × Duroc) at different stages of growth. Twelve young piglets (average BW weight of 19.0±0.33 kg) were used in this study. Pigs were divided into four phases during growing time and two phases during finishing time. The average excreta production for growing pig was 3.46 kg/head/day (feces: 1.07 kg, urine: 2.39 kg). The average moisture contents of feces and urine were 70.54% and 97.39%, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Since the turbulent kinetic energy increases with the increase of viscosity, it was found that viscosity is a very important property in describing the behavior of fluids, and it is necessary to select the property of viscosity that is most similar to pig manure. Human excrement has an average moisture content of 74.5% (63-86%) [22], which is very similar to the average moisture content (76.3%) of pig manure with a standard body weight (70 kg) [23]. Since the viscosity of human excrement is 3.5-5.5 Pa•s, in this study, the average viscosity value of human excrement, 4.5 Pa•s, was applied, and its CFD result is 0.299 J/kg, as shown Table 3.…”
Section: Analysis Parametersmentioning
confidence: 65%
“…Since the turbulent kinetic energy increases with the increase of viscosity, it was found that viscosity is a very important property in describing the behavior of fluids, and it is necessary to select the property of viscosity that is most similar to pig manure. Human excrement has an average moisture content of 74.5% (63-86%) [22], which is very similar to the average moisture content (76.3%) of pig manure with a standard body weight (70 kg) [23]. Since the viscosity of human excrement is 3.5-5.5 Pa•s, in this study, the average viscosity value of human excrement, 4.5 Pa•s, was applied, and its CFD result is 0.299 J/kg, as shown Table 3.…”
Section: Analysis Parametersmentioning
confidence: 65%
“…5 SM collected from livestock farmlands is composed of one-third of feces and two-third of urines. 49 Also, the SM slurry contains 71 wt % of water. Thus, approximately 0.5 kg of dried swine feces could be obtained per pig per day, and the estimated production of BD from each pig could reach to 22 g per day and 8 kg per year.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…As noted, the average accumulation rate of SM is 4.92 L ( i.e ., roughly equivalent to 5 kg) per pig per day . SM collected from livestock farmlands is composed of one-third of feces and two-third of urines . Also, the SM slurry contains 71 wt % of water.…”
Section: Resultsmentioning
confidence: 99%